FUNGSI PENGEMBANGAN KARIR DALAM MENINGKATKAN KINERJA PEGAWAI DI KECAMATAN BOGOR UTARA - Rafiek Firmansyah; Rita Rahmawati; Irma Purnamasari (LPPM Universitas Djuanda Bogor, 2015)
Organization, employee performance lies in the human factor (the members or employees) who carry out activities to achieve the goals of the organization itself. Employee performance is a picture of the employees who reflect the expertise, skills and abilities in addition to the employee, employee performance also reflects the willingness to work with passion. Theoretical framework is built by connecting the independent variable (X) development of a career with the dependent variable (Y) databases must address satisfying employees, the relationship between variables is described in the context of career development model of Edwin B.Flipo while the performance of employees described by Simamora, based on the theoretical framework, the operational independent variable (X) is a career development consists of six dimensions, namely: (1) the pattern and sequence of career development, (2) coordination of career development, (3) timeliness, (4) participation in career development, (5) means and infrastructure in career development, (6) the benefits of career development, employee performance while the dependent variable consists of four dimensions, namely: (1) creativity, (2) the ability of analysis and choose an alternative, (3) learning process, (4) problem solving. This study aims to determine the implementation of career development in improving the performance of employees in the District of North Bogor. The method used in this research is descriptive analysis method, which is a problem-solving procedure is investigated by using a state file subject or the object of research is happening right now based on factors that viewed the field as it should or used to describe a fact or a specific population in a systematic character, actual and fast and using the formula Weight Mean Score (WMS). Employee population is the object of observation as much as 42 people, and to determine the sample size formula used Yamane, limiting the number of samples to 31 people. Conclusions obtained from this calculation results show that the function of Career Development in Improving Performance in the District of North Bogor good interpretive criteria, even so the interview stated that there are deficiencies to be corrected.Key words: Carier, Performance, Merit System